2022
DOI: 10.1186/s12967-022-03361-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated ATF1 at Thr184 promotes metastasis and regulates MMP2 expression in gastric cancer

Abstract: Background Studies have revealed an important role of activating transcription factor 1 (ATF1) and phosphorylated ATF1 at Ser63 in tumors. Our previous study identified Thr184 as a novel phosphorylation site of ATF1. However, the role of phosphorylated ATF1 at Thr184 (p-ATF1-T184) in tumor is unclear. This study figured out the role of p-ATF1-T184 in the metastasis of gastric cancer (GC) and in the regulation of Matrix metallopeptidase 2 (MMP2). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A zinc-dependent metalloproteinase called MMP2 has been connected to angiogenesis and cancer 16 . Higher levels of the protein MMP2 were shown to be associated with better survival in Li's cohort of patients with gastric cancer 17 . MMP2, also referred to as type IV collagenase, is released in the form of an inactive proenzyme that, when activated by hydrolysis, may break down gelatin and other proteins in the extracellular matrix, which is crucial for tumor invasion and metastasis 18 .…”
Section: Discussionmentioning
confidence: 95%
“…A zinc-dependent metalloproteinase called MMP2 has been connected to angiogenesis and cancer 16 . Higher levels of the protein MMP2 were shown to be associated with better survival in Li's cohort of patients with gastric cancer 17 . MMP2, also referred to as type IV collagenase, is released in the form of an inactive proenzyme that, when activated by hydrolysis, may break down gelatin and other proteins in the extracellular matrix, which is crucial for tumor invasion and metastasis 18 .…”
Section: Discussionmentioning
confidence: 95%
“…MMPs can degrade the basement membrane and extracellular matrix, which are closely related to tumor growth, invasion, and metastasis 28 . Research has shown that the activity and expression level of MMPs such as MMP2, MMP3, MMP7, and MMP9 are increased in gastric cancer patients, which can reduce the survival period of gastric cancer patients, promote the metastasis and recurrence of cancer, and is associated with poor prognosis of gastric cancer [29][30][31] . MMP7 is secreted by tumor cells themselves, which is better as a marker of tumor progression compared to other members of the MMPs family.…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of ATF1 has been linked to early neuroectoderm differentiation of human embryonic stem cells through SRY-box transcription factor 2 (SOX2) [9]. Simultaneously, ATF1 has been implicated in promoting metastasis and regulating the expression of matrix metalloproteinase 2 (MMP2) in gastric cancer [10]. However, the regulatory mechanism of ATF1 in periodontitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%